Longevity in Cave Animals - Lunghi, Enrico; Bilandžija, Helena (Frontiers in Ecology and Evolution, 2022)
An extraordinary longevity has been observed in some cave species, and this raised the hypothesis that a longer lifespan may be considered one of the characteristic traits of these animals. However, only a few cave species have been studied thus far, and a firm conclusion remains to be drawn. Here we review the available knowledge on the longevity of subterranean species, point out the limitations of previous studies, and provide suggestions for future studies to answer important questions regarding the longevity in cave animals, its adaptive value and the related promoting factors. We also argue that studying the longevity in cave animals will contribute to the field of aging, especially to understanding the evolution of this phenomenon.